#HotForBots: Sex, the non-human and digitally mediated spaces of intimate encounter. (December 2017) - Cockayne, Daniel; Leszczynski, Agnieszka; Zook, Matthew
Contemporary practices of sex and intimacy are increasingly digitally mediated. In this paper, we identify two distinctly spatial effects of these mediations. First, the digital extends the spaces of sex/uality beyond the immediately proximate, simultaneously expanding the potential for non-human object choice in intimate encounters. Second, the digital intensifies the experiential fidelity of intimate encounters by folding the remote into the spatially immediate, such that non-proximate intimate relations with human subjects as well as non-human objects may feel more proximate. We articulate these effects by building on and contributing to developments in the geographies of encounter, which allows us to bring together theories and conceptual framings of intimacy, digitality and sexuality in a uniquely spatial register. These effects of extension and intensification resonate in a selection of empirical examples of digitally mediated sex/uality that we place along continuums of more-and-less human and more-and-less proximate. These continuums comprise the conceptual axes of a heuristic framework that we advance to both (i) capture particular points at which configurations of spaces, practices and subject/object choices of sex crystallize given conditions of pervasive digital mediation, and (ii) provoke further interrogations of the multiple ways in which sex, sexuality and intimacy are recast by the digital.